Omnibus Law: Effectiveness of Online Licensing and Law Enforcement of the Capture Fisheries Sector in Indonesia - Muslim, Shohib; Chalim, Abdul; Prasetya, Aliya Afifah; Akbarina, Farida (PT. Riset Press International, 2024)
The government has carried out the task of simplifying several laws through the ratification of Law Number 6 of 2023 concerning the Stipulation of Government Regulation in Lieu of Law Number 11 of 2020 regarding Job Creation. This initiative aims to encourage investment and increase employment opportunities. A number of articles of the old law have been amended or deleted by this regulation. One of the laws in question is Law Number 31 of 2004 concerning Fisheries. In addition, Law Number 45 of 2009 is an amendment to Law Number 31 of 2004. This study applies a normative legal research methodology, where this type of research refers to scientific investigations of legal issues by conducting research through library sources or data related to secondary license issued by the OSS Institution through an integrated electronic system. This research approach is characterized by consideration of the risk-based licensing process, not only based on licensing criteria. Apart from the main goal of increasing user convenience, individuals with limited educational levels, such as fishermen, may face challenges when trying to access the OSS system. The application and implementation of criminal law as the main legal remedy poses its own challenges. Therefore, the utilization of the criminal justice system as a means to eradicate fish theft is mainly used as a final remedy (ultimum remedium). While other sanctions, such as administrative sanctions and actions, are generally used as the main means of law enforcement.